(untitled) (Research, Society and Development, 2024)
Oxygen therapy is used to correct acute hypoxemia and alleviate symptoms in patients with lung diseases. In healthcare settings, there is a prevailing culture of administering oxygen for the wrong purposes, and this, combined with a lack of knowledge about the risks of excess oxygen, subjects patients to a condition known as hyperoxia. The main objective of the study was to evaluate the knowledge of healthcare professionals about oxygen therapy before and after the application of training. This is a prospective longitudinal study with an applied purpose, having a quantitative approach, experimental nature, and exploratory objective, with technical field research procedures. The sample consisted of 26 professionals qualified to prescribe and install oxygen therapy who work in the intensive care unit and clinical units, and for the ones who agreed to participate in the research. The intervention included training of professionals, assessment of knowledge and self-confidence about oxygen therapy, introduction of target saturation indicators, and explanation of the flowchart. After the intervention, a monitoring of for four weeks was made to assess adherence and effectiveness of the indicators. To describe the results, relative frequencies (percentages), with mean and standard deviation, nonparametric test, and Multiple Correspondence Analysis were used. Questionnaire results showed good adherence of professionals to the training, but low adaptation to its use. Therefore, we can conclude that professionals demonstrated a good knowledge level, and self-confidence before and after the training. However, the deterioration observed over time reinforces the need for local protocols to ensure the correct administration of oxygen.